EVALUASI IMPLEMENTASI PRINSIP SYARIAH PADA PRODUK MURABAHAH DAN IMPLIKASIINYA TERHADAP PERLINDUNGAN KONSUMEN DI INDONESIA - Rahmawati; Ahmad Ridha Jafar (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2026)
This study examines the gap between formal sharia principles and murabahah practices in Indonesian Islamic banking and its impact on consumer protection. Empirical findings indicate weaknesses, such as fixed margins that follow conventional interest rates and a lack of contract transparency, which have the potential to lead to hidden usury, customer misunderstanding, and economic injustice. The purpose of this study is to evaluate the implementation of sharia principles in murabahah and its impact on consumer protection. This study uses normative juridical methods, examining the fatwa of the National Sharia Council (DSN MUI) and Islamic banking regulations. The conclusion shows that although the regulatory framework and fatwas have adopted Sharia principles, the practice of murabahah tends to be administrative rather than substantive. Margins are often fixed and follow conventional interest rates, potentially giving rise to “hidden riba” and contradicting the maq??id of Sharia, such as al-?adl (justice) and ?if? al m?l (protection of wealth). Furthermore, contract transparency is often weak, with minimal disclosure of details of the cost price, margin, and payment risks, thus weakening the client's position and legal consumer protection. The novelty of this research lies in the proposal of a fairer ?iw?? (risk and effort compensation)-based margin model that aligns with the maq??id of Sharia, replacing the conventional fixed margin model. The research also recommends reformulating Sharia financial statements to reflect the values ??of the maq??id and making Sharia accounting a substantive oversight tool, rather than a mere formality. In addition, strengthened coordination between banking authorities, the Sharia Supervisory Board, and regulatory institutions is proposed to ensure more effective and sustainable operational oversight and compliance with principles. Keywords: Murabahah Products, Consumer Protection, Implementation of Sharia Principles